Unstable Upper Cervical Spine Injury with Concomitant Bilateral Ponticulus Posticus: A Case Report - Fujisawa, Masashi; Wakahara, Sota; Inamasu, Joji (Asian Journal of Neurosurgery, 2025)
Ponticulus posticus (PP), also known as arcuate foramen, is an anatomical variation of the atlas (C1), which is an ossification of the posterior atlanto-occipital membrane and through which the V3 segment of the vertebral artery (VA) runs. Placement of a polyaxial screw in the C1 lateral mass is considered risky in those with PP because of possible risk for VA injury. We report a case with bilateral PP in which posterior fixation for unstable upper cervical spine injury was performed. The patient, a 70-year-old man, sustained a fall-induced unstable upper cervical spine injury (traumatic C2 spondylolisthesis with unilateral dislocation of the C3-4 facet joint). Following initial conservative treatment, a posterior fixation surgery was performed in the subacute phase. Preoperative images revealed the presence of bilateral PP. Therefore, an original plan to place the screws in the C1 lateral mass was discarded, and instead, placement of the laminar hook on one side and placement of the screw into the C1 posterior arch on the other side was performed. His postoperative course was uneventful, and he was transferred to a rehabilitation hospital 27 days after the injury. In cases of upper cervical spine instability with concomitant PP, it is essential to consider the fixation method based on the extent of the injury and the course of the VA on a case-by-case basis.
Keywords: upper cervical spine injury; vertebral artery; ponticulus posticus; lateral mass screw; arcuate foramen